2018
DOI: 10.1080/00219266.2018.1490798
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions in biology: a meta-synthesis study of research, 2000–2014

Abstract: Teachers need to be aware of biology misconceptions in their classrooms and how to address them. In response, researchers and science educators have suggested and examined effective practices to prevent and ameliorate misconceptions. An extensive review of the literature gives researchers and educators insights into trends, practices, and gaps in the misconceptions research and helps decide which issues to address and why. The current study shares how researchers in Turkey conduct a content analysis of publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
0
17
0
3
Order By: Relevance
“…• Effectiveness of CCS has not been empirically and significantly evidenced in the literature Kumandaş, Ateskan and Lane (2018), through a meta-synthesis study, revealed that though many articles showcased the use of CCS to clear misconceptions, only few studies have thoroughly tested the efficiency of the strategy.…”
Section: Strategies To Identify and Clear Misconceptionsmentioning
confidence: 99%
“…• Effectiveness of CCS has not been empirically and significantly evidenced in the literature Kumandaş, Ateskan and Lane (2018), through a meta-synthesis study, revealed that though many articles showcased the use of CCS to clear misconceptions, only few studies have thoroughly tested the efficiency of the strategy.…”
Section: Strategies To Identify and Clear Misconceptionsmentioning
confidence: 99%
“…Despite the substantial body of literature on misconceptions in both psychology (Furnham & Hughes, 2014;Lilienfeld, 2012;Lyddy & Hughes, 2012) and biology (Brumby, 1984;Bahar, 2003), little is known about misconceptions that intersect both fields. Specifically, little is known concerning students' understanding (and misunderstanding) of biological and environmental influence on human development and, critically, about their understanding and misunderstanding of how these factors interact.…”
Section: Interdisciplinary Phenomena and Misconceptionsmentioning
confidence: 99%
“…Misconceptions compromise learning, especially for meaningful learning. More than just memorising facts, it occurs when students make connections and relate between new knowledge and prior knowledge (Kumandaş, Ateskan & Lane, 2019). However, students find it challenging to connect them.…”
Section: Introductionmentioning
confidence: 99%